2010
DOI: 10.17221/202/2009-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Contents of major phenolic and flavonoid antioxidants in selected Czech honey

Abstract: Lachman J., Hejtmánková A., Sýkora J., Karban J., Orsák M., Rygerová B. (2010): Contents of major phenolic and flavonoid antioxidants in selected Czech honey. Czech J. Food Sci., 28: 412-426.The chemical constitution of antioxidants contained in honey is derived from its origin. Forty honey samples (harvest 2006), which came from various locations of the Czech Republic and varied in their origins, were evaluated spectrophotometrically for their total polyphenol content, total flavonoids and 3',4'-dihydroxyflav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 25 publications
4
39
2
2
Order By: Relevance
“…and Acacia spp. Multifloral honey that came from Sbeirreh and Ras Moneif also had low total phenolic compound values (37.5 and 40.2 mg/ 100 g, respectively), while the other values ranged between 44 and 58 mg/100 g. Lachman et al (2010a) reported that the total phenolic content varied from 32.59 mg/100 g in multifloral honey to 93.66 mg/100 g in honeydew honey. Pollen analysis also shows that nine honey samples are considered a multifloral honey obtained from different floral origin.…”
Section: Resultsmentioning
confidence: 96%
“…and Acacia spp. Multifloral honey that came from Sbeirreh and Ras Moneif also had low total phenolic compound values (37.5 and 40.2 mg/ 100 g, respectively), while the other values ranged between 44 and 58 mg/100 g. Lachman et al (2010a) reported that the total phenolic content varied from 32.59 mg/100 g in multifloral honey to 93.66 mg/100 g in honeydew honey. Pollen analysis also shows that nine honey samples are considered a multifloral honey obtained from different floral origin.…”
Section: Resultsmentioning
confidence: 96%
“…The most pronounced difference in the trace elements contents was that between honeydew and blossom honeys (Ivanov & Chervenakova 1984;Feller-Demalsy et al 1989;Sevlimli et al 1992). The differences in the contents of metals between the individual monofloral honey samples could be related to different compositions (Lachman et al 2010). This can explain higher levels of Al, As, Cu e.g.…”
Section: Resultsmentioning
confidence: 99%
“…37,38 Diğer ül-kelerde yapılan araştırma sonuçları ile karşılaştırıl-dığında ise türler arası ve bölgesel farklılığa bağlı değişkenlik göstermektedir (Tablo 3). 25,43 Çalışmada total antioksidan aktivitesinin hesaplanması, balın DPPH üzerinde serbest radikal süpü-Örnekler Total flavonoid (mgQE/kg) (min-max) Total fenolik mgGAE/kg) (min-max) Antioksidan, DPPH-sc 50 (mg/ml) (min-max) …”
Section: Discussionunclassified